Application Possibilities Artificial Intelligence (AI) in Physical Education - Karap, Bálint; Müller, Anetta; Horváth, Tamás; Laoues-Czimbalmos, Nóra; Biró, Melinda (Acta Carolus Robertus, 2025)
In our research, our aim was to examine the opinions of educators (elementary school teachers, preschool teachers, and physical education teachers) regarding the potential applications of artificial intelligence (AI). Our goal was to explore how the surveyed educators perceive AI in relation to physical education, and in which areas professionals believe it could be applied in their own work during physical education sessions. We used a questionnaire-based method in our research. A total of 383 individuals participated in the study. The sample (N=383) consisted of 33.15% elementary and preschool teachers and 66.84% physical education teachers. The results indicated that the participants of the research saw the greatest significance of AI use in data collection, skill development, and the implementation of individualized development programs. Artificial intelligence can support the work of teachers in many ways. However, teachers must also understand the potential of AI and how to use it. We agree with authors such as Hyun and Junga (2021) and Fatih (2025), who emphasize that future physical education teachers must possess technological and AI expertise to effectively integrate AI tools.
Keywords: Artifical Intelligence; education; physical education